The Relationship between Exercise Addiction, Physical Activity Level and Body Mass Index of the Students Who are Studying at Physical Education and Sports College - GUN, Adem; AGIRBAS, Ozturk (Asian Journal of Education and Training, 2019)
Context: The aim of the study was to identify the relationship between exercise addiction (EA) and physical activity levels (PAL) and body mass index (BMI) of students of Physical Education and Sports College (PESC). Methods: The study consists of 204 male and 101 female from Erzincan University PESC. Personal Information Form, Exercise Dependence Scale-21 and Physical Activity Survey were used. The data were analyzed in SPSS22.0 for windows. Kruskal-Wallis-H, Mann-Whitney-U and Spearman Correlation tests were used. Results: It was detected that % 13,2 of male students of PESC, % 15.8 of female students and % 14.1 of students in general were exercise addicted, while there was no significant difference between BMI according to the EA status of male students of PESC, the PAL of exercise addicted and candidate of addiction was statistically significantly higher in comparison with non-addict, according to the EA status of female students of PESC there was no significant difference between neither MBI nor PAL, the BMI of male students of PESC is significantly higher, the PAL values of candidates of EA is significantly higher, there was no significant differences between BMI and PAL values of the students according to the family economic level, there was no significant relationship neither male nor female students between BMI and PAL according to the EA levels. Conclusion: It was extrapolated that, few of the students are EA; the students who are high in EA are also high in PAL values, the family economic, level on the students’ EA level is not an effective factor, and also there was no significant relationship between BMI and PAL according to the EA status.